2011
DOI: 10.1111/j.1600-0463.2010.02708.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic characteristics and steroid response of IgM nephropathy in children presenting with idiopathic nephrotic syndrome

Abstract: There is no detailed information on clinical and immunopathologic features of immunoglobulin M nephropathy (IgMN) in children with idiopathic nephrotic syndrome (INS) in Pakistan. We reviewed our native renal biopsies over 15 years (July 1995-July 2010) and identified 135 cases of IgMN in nephrotic children (≤17 years). Their demographic, clinical and immunopathologic data were retrieved from biopsy reports and case notes. Mean age of this cohort was 7.6 ± 4.2 years. Males were 92 (68.1%) and females were 43 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
54
0
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(65 citation statements)
references
References 20 publications
6
54
0
5
Order By: Relevance
“…This is not as per our study as we had a majority of cases with SDNS (65%) with 30% having SRNS. But our data correlates with another study done from South Asia (Pakistan) who found 34.2% children to have SRNS [6] . However, there is an inherent bias in the selection of paediatric patients with NS for renal biopsy (indications are as mentioned in our methodology).…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…This is not as per our study as we had a majority of cases with SDNS (65%) with 30% having SRNS. But our data correlates with another study done from South Asia (Pakistan) who found 34.2% children to have SRNS [6] . However, there is an inherent bias in the selection of paediatric patients with NS for renal biopsy (indications are as mentioned in our methodology).…”
Section: Discussionsupporting
confidence: 78%
“…A study done in Saudi Arabia [23] showed that 18 out 36 patients had hematuria whereas another study from neighbouring Bangladesh [24] showed a case report which also had hematuria on presentation. Another article from neighbouring Pakistan [6] showed presence of hematuria in 31.2% children (42/135). The detailed analyses are as mentioned in TABLE 2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the studies have reported on prevalence of IgMN as frequency/ percentage of renal biopsies with diagnosis of IgMN reported from 2 % to 18.5 % in native biopsies (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Occasional cases of IgMN in transplant biopsies have also been reported (14).…”
Section: Epidemiologymentioning
confidence: 99%